Speech Dysfluence and Memory Processing: Language Disorders in the Indonesian Television Series - Adawiyah, Robi'ah; Istiqomah, Fina Zaidatul (SUAR BETANG, 2025)
Speech disfluency is a language phenomenon that often occurs during spontaneous oral communication, especially on interactive media such as television. This study aims to explore the forms and factors that cause disfluency in the television series Arisan. The method in this study uses Qualitative with a descriptive approach. Data were obtained through observation and documentation studies of dialogues broadcast in December 2024. Data collection techniques in this study used direct observation and documentary studies. While the data analysis technique used in this study was content analysis. The results of the study revealed that disfluency in Arisan! can be classified into four main types: repetition, pauses, speech repair, and use of filler words. These four types can occur at various levels, from words, syllables, to phrases. This is caused by unpreparedness or immature speech planning, psychological factors such as nervousness, mental burden, and situational pressure as well as social factors such as interaction with the interlocutor and listener expectations also contribute to the emergence of disfluency. This study shows that disfluency is not only a barrier in communication, but also part of the speaker's adjustment strategy in managing spontaneous verbal interactions. With this study, it is expected to be a source of knowledge related to the phenomena of language disorders that appear in daily activities.